Publishing Practices Among Senior Multidisciplinary Researchers Using Turnitin.com Originality Reports - Jun S Camara; Dr Randy Joy M Ventayen (ASEAN Multidisciplinary Research Journal, 2020)
A researcher cannot publish what he has not written, and he cannot write what he has not read – that is how vital the central role of reading is in a researcher’s academic life. This study, an excerpt, aimed to identify the publishing practices among senior multidisciplinary researchers by analysing the originality reports of their published articles generated through the Turnitin.com software. Findings showed that the published articles are organized and intact and are structured using the IMRAD format. Quantitative analysis showed that while there was a moderate positive correlation,  there is no significant difference between the total number of references listed in the published articles and with their generated similarity indices. Statistical analysis revealed that the published articles serving as ‘document transcripts’ had more similarity from internet-based articles rather than from publication-based sources. While the findings agree with similar reviewed studies that publication sources are used less in publication practice, the study has established that senior researchers used publication-based studies more often than undergraduate researchers. Evidence that empirical studies are consulted less during publishing in multidisciplinary journals in the Philippines is conclusive. Thus, it is recommended that senior authors develop the attitude of making their research profile visible in the web by creating web-based research profile accounts.